1999
DOI: 10.1107/s0909049599001090
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature EXAFS study of solid and liquid rhodium

Abstract: Accurate EXAFS spectra of solid and liquid rhodium at very high temperature were recorded at the E.S.R.E (BM29, Grenoble) The short range g(r) was determined using reliable EXAFS data-analysis methods based on ab-initio multiple scattering calculations. Experimental results were compared with moleculardynamics (MD) calculations. The first neighbor distribution departs from a simple Gaussian model, even at moderate temperatures in the solid phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Due to the advance of modern EXAFS algorithms and the availability of more accurate ion and solvent potential models, the number of studies that combine MD with EXAFS has increased considerably. Our work is distinguished from early contributions in that we combine MD, ab initio quantum chemical calculations and EXAFS measurement to address the ion solvation in aqueous solution. We have recently developed a method to predict EXAFS spectra: an ensemble of molecular configurations is generated from an intermolecular potential and is subsequently used in electron scattering analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the advance of modern EXAFS algorithms and the availability of more accurate ion and solvent potential models, the number of studies that combine MD with EXAFS has increased considerably. Our work is distinguished from early contributions in that we combine MD, ab initio quantum chemical calculations and EXAFS measurement to address the ion solvation in aqueous solution. We have recently developed a method to predict EXAFS spectra: an ensemble of molecular configurations is generated from an intermolecular potential and is subsequently used in electron scattering analysis.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of the present theory, the number and type of surrounding atoms, their average distance to the central absorbing atom, and their distribution about the absorbing center can be ascertained. A more complete understanding of the structural information contained in the EXAFS spectra has been derived in many instances from MD simulations of the aqueous system. In standard EXAFS analysis, the fine structure factor is defined by where μ( E ) is the absorption coefficient as a function of the X-ray energy E = E 0 + ℏ 2 k 2 /2 m e , μ 0 ( E ) is the background absorption coefficient, and Δμ 0 ( E 0 ) is the jump in the absorption background at the absorption edge, E 0 . EXAFS spectra provide predictions of the number of water molecules in the first solvation shell, which is the average distance of these scatterers from the central atom, and a measure of the static disorder of this first solvation shell, as well as the vibrational disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The inadequacy of the harmonic approximation in describing thermal vibrations, especially at high temperatures, has been studied in several other cases including those of metals (see [5,6] and references therein) and superionic salts (see [7,8] and references therein). In particular, detailed studies of simple solid metals at high temperature such as Cu [5] and Rh [6,9] have shown that a deep insight into the atomic interaction can be gained by looking at the evolution of the low-order cumulants of the first-shell distribution as a function of temperature. In a recent paper [10], it has been shown that the shape of an effective pair potential describing the interatomic interaction in MD simulations of solid Rh can be refined using first-neighbour pair distribution functions determined by XAS at various temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The inadequacy of the harmonic approximation in describing thermal vibrations, especially at high temperatures, was studied in several other cases including metals (see [5,6] and references therein) and superionic salts (see [7,8] and references therein). In particular, detailed studies of simple solid metals at high temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, detailed studies of simple solid metals at high temperatures (e.g. Cu [5], Rh [6,9] and Pb [10]) demonstrated that a deep insight into atomic interactions can be gained by looking at the evolution of the first cumulants of the first-shell distribution as a function of temperature. It was shown in [11] that the shape of an effective pair potential describing interatomic interactions in MD simulations of solid Rh can be refined using first-neighbor pair distribution functions determined by XAS at various temperatures.…”
Section: Introductionmentioning
confidence: 99%